1992
DOI: 10.1038/ki.1992.42
|View full text |Cite
|
Sign up to set email alerts
|

Glomerular cell proliferation and PDGF expression precede glomerulosclerosis in the remnant kidney model

Abstract: Increasing evidence supports a role of glomerular cell proliferation in the development of focal or diffuse glomerulosclerosis. This study investigates the chronology and sequence of cellular events that precede glomerulosclerosis in 5/6 nephrectomized rats. Within three days of renal ablation, a phenotypic switch occurred in which some mesangial cells expressed alpha-smooth muscle actin. This was followed by proliferation of mesangial cells, and to a lesser degree endothelial cells from day 5 to week 4 as det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

14
249
1
5

Year Published

1997
1997
2012
2012

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 381 publications
(269 citation statements)
references
References 40 publications
14
249
1
5
Order By: Relevance
“…05 versus PDGF 10 ng/ml without adiponectin). demonstrating increased MC proliferation and glomerular PDGF expression in the five out of six nephrectomized rats, which were well-established models of CKD (Floege et al 1992). These findings suggest that PDGF-induced RMC disorders in the glomeruli may contribute to glomerular injury leading to CKD.…”
Section: Discussionmentioning
confidence: 82%
“…05 versus PDGF 10 ng/ml without adiponectin). demonstrating increased MC proliferation and glomerular PDGF expression in the five out of six nephrectomized rats, which were well-established models of CKD (Floege et al 1992). These findings suggest that PDGF-induced RMC disorders in the glomeruli may contribute to glomerular injury leading to CKD.…”
Section: Discussionmentioning
confidence: 82%
“…2,22,23 Several studies have shown that both platelet-derived and transforming growth factors, as well as TNF␣ may play a role in the pathogenesis of glomerular injury. 6,7,24,25 TNF␣ enhances the expression of intercellular adhesion molecule-1 (ICAM-1) 9 and blood levels of ICAM-1 were found to be increased in atherosclerotic hypertensive subjects with preserved renal function, suggesting a systemic endothelial dysfunction. 26 Furthermore, on the basis of experimental results Liu et al 27,28 hypothesised that in hypertension, vascular thrombotic risk is associated with Table 1 Mean age, serum creatinine and creatinine clearance (Clcr), blood levels of TNF␣ and ET-1, UAE, 24-h systolic-(SBP), diastolic (DBP) and mean (MBP) blood pressures in normotensive controls (NT), in patients with essential hypertension (EH), and in hypertensive subjects with renal insufficiency (CRF)…”
Section: Discussionmentioning
confidence: 99%
“…In treated and untreated animals, PDGF synthesis increased from weeks 16 to 24, despite considerable reduction of infiltrating cells. Since PDGF is produced not only by platelets, but by mesangial cells as well [12], it is suggested that glomerular cell proliferation may become self-perpetuating by an autocrine mechanism involving mesangial cell production of PDGF [12]. Therefore, PDGF may be more important for the later progression of CAN than TGF-P1.…”
Section: Discussionmentioning
confidence: 99%